Effect of a probiotic fermented milk on the thymus in BALB/c mice under non-severe protein-energy-malnutrition - Novotny Núñez, Ivanna (2013)
Protein–energy malnutrition (PEM) causes a significant impairment of the immune system, the thymus being one of the most affected organs. It has been demonstrated that the administration of probiotic fermented milk (PFM) recovered the intestinal barrier, histological alterations and mucosal and systemic immune functions in a non-severe malnutrition model using BALB/c mice. The aim of the present study was to evaluate, in the same model of malnutrition, the effect of a PFM added to a re-nutrition diet on the recovery of the thymus, analysing histological and functional alterations caused by malnutrition. Mice were undernourished and divided into three groups according to the dietary supplement received during re-nutrition: milk, PFM or its bacterial-free supernatant (BFS). They were compared with well-nourished and malnourished mice. PFM was the most effective re-nutrition supplement to improve the histology of the thymus, decreasing cellular apoptosis in this organ and recovering the percentage of CD4þ/CD82 single-positive thymocytes. Immature doublepositive thymocytes were increased in the malnourished control (MC). The production of different cytokines in the thymus was increased in mice given PFM, compared with the mice that received other dietary supplements and MC. Mice given the BFS presented an improvement in the thymus similar to those that received milk. We demonstrated the importance of the whole PFM supplementation on the histological and functional recovery of the thymus in a non-severe PEM model.